A Case of Common Variable Immunodeficiency with CREBP Gene Mutation without Rubinstein Taybi Syndrome Features. (4th July 2022) - Musabak, Ugur; Ceylaner, Serdar; Erdogan, Tuba; Ayva, Ebru Sebnem
Abstract : Hypogammaglobulinemias, based on inborn errors of immunity, are primary immunodeficiencies (PIDs) that can also be diagnosed for the first time in adulthood. Common variable immunodeficiency (CVID) is a multifactorial disease often symptomatic due to antibody deficiency. In addition, some PIDs are classified into the category of immunodeficiencies with syndromic features due to their accompanying clinical findings unrelated to immunity. In this article, a patient with CVID who was diagnosed in adulthood and who was revealed to have a mutation specific to Rubinstein–Taybi syndrome and clinical features reminiscent of this syndrome only after molecular tests was presented.